To trust the Other. Anthropology of education in the context of Polish debates on multiculturalism - Drozdowicz, Jarema (Wydawnictwo Naukowe WH, 2013)
The article presents selected critical trajectories in the specific Polish debate on multiculturalism within the context of a much wider issue of otherness. This is considered as a major issue in current social and political debates because if the fact, that Polish society in its most general terms is still widely associated as a culturally homogenous community, where every single evidence of cultural otherness is being treated more or less as a threat to national identity. Therefore we are forced to ask if in contemporary conditions the vision of a homogenous Polish national community can be still held as dominant? Multiculturalism can in this light be an ideology, as well a social praxis. This problem is being put in the paper in the wide spectrum of a specific discipline which deals with cultural otherness, i.e. cultural anthropology, or to be more specific anthropology of education. Anthropological encounters with the cultural Other build up a central figure in the discipline’s dictionary. The category of cultural difference itself had made a long lasting career in this field of knowledge, since the beginnings of the anthropological reflection on man as a culturally defined being. This paper takes the anthropological perspective and puts it into the field of current shifts visible in the contemporary Polish society. The main question here is therefore tackling the sensible issue of trust expressed in cultural terms, not just through declarative politics of multiculturalism.
Keywords: anthropology of education; educational anthropology; poland; multiculturalism; Europe; education; discourse; nation state; otherness